Home away from home - Akbari, Nazneen (Barefoot Books, 2026)
Nuha is already worried about spending the summer in Oman. When she leaves behind her dearest doll, how will she possibly feel at home now? Her Jadda brings her through the souk (market) to find a new treasure, and Nuha slowly finds that Oman is special in its own way. It may even start to feel a bit like home.